Synthesis of Leaf‐Vein‐Like g‐C3N4 with Tunable Band Structures and Charge Transfer Properties for Selective Photocatalytic H2O2 Evolution - Feng, Chengyang; Tang, Lin; Deng, Yaocheng; Wang, Jiajia; Luo, Jun; Liu, Yani; Ouyang, Xilian; Yang, Haoran; Yu, Jiangfang; Wang, Jingjing (Advanced functional materials, 2020)
Photocatalytic H2O2 evolution through two‐electron oxygen reduction has attracted wide attention as an environmentally friendly strategy compared with the traditional anthraquinone or electrocatalytic method. Herein, a biomimetic leaf‐vein‐like g‐C3N4 as an efficient photocatalyst for H2O2 evolution is reported, which owns tenable band structure, optimized charge transfer, and selective two‐electron O2 reduction. The mechanism for the regulation of band structure and charge transfer is well studied by combining experiments and theoretical calculations. The H2O2 yield of CN4 (287 µmol h−1) is about 3.3 times higher than that of pristine CN (87 µmol h−1), and the apparent quantum yield for H2O2 evolution over CN4 reaches 27.8% at 420 nm, which is much higher than that for many other current photocatalysts. This work not only provides a novel strategy for the design of photocatalyst with excellent H2O2 evolution efficiency, but also promotes deep understanding for the role of defect and doping sites on photocatalytic activity. Leaf‐vein‐like g‐C3N4 synthesized via a KBH4‐assisted thermal polycondensation strategy exhibits enhanced optical absorption, efficient charge carrier separation, and ample active sites, accordingly enabling excellent photocatalytic H2O2 evolution. The synergistic effect of B doping and defect sites on the improvement of catalyst performance is fully discussed by experiments and density functional theory calculations.